Sistem Informasi Geografis Berbasis Web Untuk Pemetaan Penerima BPJS Dengan Algoritma Dijkstra - Muhamad Reynaldi Rendi; Rachmat Wahid Saleh Insani; Asrul Abdullah (UNIB Press, 2026)
The Sungai Raya Village apparatus faces challenges in managing BPJS beneficiaries due to the lack of mapping and route optimization tools. This research aims to build a web-based Geographic Information System (GIS) to visualize recipient locations and implement Dijkstra's Algorithm for determining the shortest visit routes. Developed using Laravel, MySQL, and Leaflet.js following the Waterfall methodology, the system successfully maps data with hamlet-based filtering features. Testing confirms that Dijkstra's Algorithm generates valid routes, which were verified against Google Maps. Black Box testing showed all functions perform correctly, and User Acceptance Testing (UAT) yielded a score of 81.75%. These results indicate the system effectively supports the efficiency of data verification and field visit planning.